A dynamic and spatially explicit psychological model of the diffusion of green electricity across Germany. (October 2017) - Ernst, Andreas; Briegel, Ramón
Abstract: Green energy, i.e. electricity stemming from renewable resources, can help mitigate climate change. This paper presents a social simulation (or agent-based model) that aims going one step in validating a dynamic psychological decision micro-theory that has been developed to include goals, deliberative decisions as well as status quo bias, social milieus, communication over personal networks, and sensitivity towards external events such as price changes or messages from the media. We show how the simulation replicates a set of customer data from a German green energy provider, reproducing the temporal and spatial diffusion of adoption of their product. The building of the simulation is supported by a survey (N = 778) investigating the psychological variables relating to the adoption of green energy and lifestyles (milieus), and online experiments about personal networks and information processing style. A scenario, i.e. an experiment run within the simulation, introduces more frequent communication between households that is interpreted as the effect of an information campaign. The frequency of personal communication and a salient event reported in the media interact to foster green energy adoption. We argue that social simulation proves being an appropriate tool to develop and test dynamic psychological theories.